PENGARUH PENGGUNAAN MULTIMEDIA ANIMASI MELALUI MODEL KOOPERATIF TIPE STAD TERHADAP KETERAMPILAN BERPIKIR KRITIS OLEH SISWA - laila kurniawati; Arwin Achmad; Rini Rita T Marpaung (Universitas Lampung, 2013)
Critical thinking skills should be owned by everyone. Observations indicate that the students’ thinking skills of class IX SMP N 8 Bandar Lampung had been developed. Therefore, it is necessary to act as a solution to improve the students’ thinking skills. One way to use multimedia animation through cooperative learning model STAD type. This research aimed to find out the effect of the use of multimedia animation with cooperative learning model STAD type to the students' thinking skills on the subject matter of the Human Reproductive System.The research design was pretest-posttest design are not equivalent. The research sample is class IX A and IX B are selected from the population at random cluster sampling. Quantitative data obtained from the average value of the pretest, posttest, and N-gain satistik analyzed. Qualitative data in the form of student activity data taken using the rubric student activity data and student responses to learning using multimedia animation with type STAD cooperative learning model that analyzed descriptively. The results showed that the use of multimedia animation with cooperative learning model STAD type significantly affect toward students' thinking skills. In addition, an increase of students critical thinking in the experimental class with an average N-gain 63.95% is medium criteria, on average N-gain of all the indicators of students in the experimental class students' thinking skills also increased the amount of 65.88% with criteria being. The average percentage of student learning activities in all aspects of that observed in the experimental class has medium criteria 71.75%. In addition, most students responded positively to the use of multimedia animation through cooperative learning model STAD type. Keywords: Multimedia Animation, STAD, critical thinking skills, The Human Reproductive System